Effects of gonadal hormones on thymus gland after bilateral ovariectomy and orchidectomy in rats - Öner, H; Ozan, E (Taylor & Francis Inc, 2002)
This study examined the histological changes that occurred in the thymus gland after gonadectomy and the administration of various sex steroids following gonadectomy. Male and female Wistar-albino rats that were 6 weeks of age were used. The rats were subjected to bilaterally gonadectomy and then gonadal steroid hormones (testosterone. estrogen, and progesterone, 2.5 mg/kg) were given. Effects of gonadal steroid hormones on the thymus gland were microscopically examined. Thymic weight increased in all the groups after gonadectomy, Testosterone, estrogen, and estrogen + progesterone treatment decreased thymic weight after gonadectomy. Progesterone treatment also decreased weight, but there was no statistical significance. In the light microscopy, testosterone and estrogen treatment induced a loss of lymphoid elements from the thymic cortex, increased the number of phagocytic macrophages and mast cells, and enlarged blood vessels and connective tissue were observed in the thymic medulla, In the electron microscopic study it was observed that rough endoplasmic reticulum enlarged in the thymic lymphocytes. The same results were also found after estrogen + progesterone treatment. No histologically identifiable changes were observed in the thymus gland after progesterone treatment. This study demonstrated that the thymus gland undergoes involution after testosterone and estrogen treatment, but not progesterone, following gonadectomy.
Keywords: estrogen; rnicroscopy; progesterone; testosterone; thymus gland